THE INTELLECTUALS OF THE COMMUNIST PARTY DURING THE POPULAR FRONT (ARGENTINA, 1935-1946) - Piro Mittelman, Gabriel Omar (Revista de Historia Social y de las Mentalidades, 2022)
This work analyzes, through various sources, the activity of intellectuals linked to the Communist Party of Argentina (CP) in relation to its Popular Front political strategy, from the mid-30s, until the prolegomena of Peronism in 1946. From the analysis of their political practice, we will argue that intellectuals linked to the CP, through the establishmentof a varied network of cultural, personal and institutional relationships, played an important role in bringing the party closer to sectors of radicalism, socialism, and the "democratic parties" with which it intended to ally.